Symptomatic hamulus-pisiform coalition in a 53-year-old woman with a flexor carpi ulnaris pain - Habbachich, Hamza; Ladjimi, Alexandre; Malinowska, Marta; Elkazzi, Wissam (International Journal of Research in Orthopaedics, 2025)
Hamulus-pisiform coalition is a rare form of carpal bone fusion that is usually asymptomatic but can occasionally cause chronic wrist pain and ulnar neuropathy. We present the case of a 53-year-old woman with persistent ulnar-sided wrist pain lasting over a year despite multiple corticosteroid injections and physiotherapy. Imaging confirmed a complete osseous fusion between the pisiform and hamulus of the hamate bone, accompanied by moderate chronic enthesopathy of the flexor carpi ulnaris tendon. Due to ongoing symptoms and failure of conservative management, surgical excision of the coalition was performed. Three weeks postoperatively, the patient experienced complete pain relief and full recovery of wrist range of motion. This case emphasizes the importance of considering hamulus-pisiform coalition as a possible diagnosis in patients presenting unexplained ulnar-sided wrist pain nonresponding to conservative treatment.